Characterization of the Microstructure after Composite Peening of Aluminum. Issue 2 (6th September 2020) - Seitz, Michael; Dürrschnabel, Michael; Kauffmann, Alexander; Kurpiers, Chantal; Greiner, Christian; Weidenmann, Kay André
Abstract : Composite peening is a novel process to introduce ceramic blasting particles into the surface of substrates. Depending on the process parameters, the penetration depth of the blasting particles can be several micrometers. In previous investigations by some of the authors, it has been found that the ceramic particles incorporated during composite peening are significantly smaller compared to 10 μm in size before peening. Herein, the microstructure after composite peening is highlighted. To investigate this microstructure, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) are performed. The subsequent X‐ray diffraction (XRD) analysis provides further evidence of a severely deformed, nanocrystalline ceramic layer consisting of fragmented blasting particles. Abstract : The purpose of composite peening is to introduce ceramic particles into an aluminum matrix. Herein, the microstructure after composite peening is investigated using scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X‐ray diffraction. The penetrated blasting particles of alumina are present as nanometer‐sized fragments with a high defect density.